The effect of environmental governance in quality improvement of urbanization—Evidence from China 2000–2017 - Tang, Zhiguo; Tian, Yanping; Yu, Shuyi (Frontiers in Environmental Science, 2023)
This paper constructs an evaluation index system for urbanization quality based on a new development philosophy by the Chinese government and adopts the entropy value method to investigates the effect of environmental governance using provincial panel data from 2000 to 2017. The empirical results are as follows. Firstly, the overall effect of environmental governance on improving the quality of urbanization is significant, however, among the environmental governance effects of the five dimensions of urbanization quality, it is conducive to innovation and coordinated development but not conducive to shared development. Secondly, the role of the three governance mechanisms in the environmental governance system is not balanced. The contributions of market governance is much higher than that of government governance and public governance, And there is a large room for improvement in the effectiveness of collaborative governance. In terms of the improvement of specific dimensions of urbanization quality, government governance contributes significantly to innovative development but restricts open and shared development; market governance promotes green and shared development but inhibits open development; public governance plays a positive role in coordinated and open development but hinders innovative, green and shared development. Thirdly, the role of environmental governance has significant regional differences. The eastern region is high, the northeast and central regions are second, and the western region is a negative effect. Within the environmental governance system, government governance has a significant promoting effect on all regions, market governance has a significant promoting effect on eastern, western, and northeastern regions. And public governance has the largest promoting effect on eastern and central regions, while it has an inhibiting effect on western and northeastern regions. In the future, it is necessary to build an environmental governance system adapted to the regional reality, play the leading role of government environmental regulation, and optimize the collaborative mechanism of the government, enterprises and the public in the environmental governance system with the guidance of market governance.